Ethical dimensions of (journalistic) representations and reporting of The other - Donev, Dejan (Odsek za medijske studije, Filozofski fakultet, Novi Sad, 2011)
Wherever a man turns, he sees people. A man lives among people, surrounded by people, with people. In modern era, we learned seeing “the other” with opened eyes and heart. In this, we got a lot of help from existentialists and also from the philosophers who defended ethics as the first philosophy, like for example Emmanuel Levinas. However, from that sum of people, some are really close to us even often they are not our relatives, or more important not part of our family, not friends in classical way of thinking, not even working together…, but still for us very close people - and those are our neighbors. The communication between neighbors is specifically characterized with, above all, the ethical dimension that is contained in it, e.g. the ethical values, goals and standards which are included in it, and which are defined from the essentiality and the meaning of the neighborhood as a social and anthropological relation. From here, the phenomenology of the neighborhood is really interesting for exploring. It’s about the personal quality of “the other” as a neighbor which results with the intimacy among people and with specialized relations between them. In the cognition of the same, very specific role has the media, which have the key role and responsibilities for spreading and promoting those important values and relationships that are initial and essential for building and constructing of a real democratic society. The way they do the same within Macedonian society, trying to reflect the differences, as well as the presence of the difference within their own media structure and journalistic contents that they are placing, is the theme that author deals in this text.
Етичките димензии на (новинарското) претставување и известување за другиот
Edicija Medijska istraživanja, Zbornik radova III - Digitalne medijske tehnologije i društveno-obrazovne promene
Keywords: Ethics of The Other, media, ethical journalism, neighbors, phenomenology of the neighborhood, relationships, real democratic society